Luteal-phase support in assisted reproductive technology: An ongoing challenge - Saeideh Dashti; Maryam Eftekhar (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract It has been shown that in controlled ovarian hyper stimulation cycles, defective luteal phase is common. There are many protocols for improving pregnancy outcomes in women undergoing fresh and frozen in vitro fertilization cycles. These approaches include progesterone supplements, human chorionic gonadotropin, estradiol, gonadotropin-releasing hormone agonist, and recombinant luteinizing hormone. The main challenge is luteal-phase support (LPS) in cycles with gonadotropin-releasing hormone agonist triggering. There is still controversy about the optimal component and time for starting LPS in assisted reproductive technology cycles. This review aims to summarize the various protocols suggested for LPS in in vitro fertilization cycles.